The Influence of Food Creation Activity on the Improvement of Picky Eater Behavior in Children Aged 5-6 Years in TK Negeri Pembina in Pemalang Regency - Windiyani, Amalia Ayu; Mukminin, Amirul (BELIA: Early Childhood Education Papers, 2021)
This study aims to determine whether the food creations activity can overcome the picky eater behavior of children aged 5-6 years. This research is a type of quantitative research using the Pre-Experimental Design method with the One Group Pretest-Posttest Design approach. The subjects in this study are children aged 5-6 years or TK B in TK Negeri Pembina, Pemalang Regency, totaling 30 children. The data collection technique used is an instrument in the form of a questionnaire using a Likert scale. Data analysis techniques are descriptive statistics and Paired Sample T-Test. All calculations are processed using IBM SPSS 20. Based on the results of the Paired Sample T-test calculation, the value of tcount > ttable (13.482 > 2.045) with a significance value of 0.000. Therefore, Ho is rejected and Ha is accepted. In other words, that there are differences in the average pretest and posttest results, which means that there is an influence on the activity of forming food creation in overcoming picky eater behavior of children aged 5-6 years. A significant difference can be seen from the value of sig (2 tailed) < 0.05 which is 0,000. This means that the application of activities to form food creations in this study can overcome the picky eater behavior of children aged 5-6 years. An increase in the mean value of picky eater behavior improvement in children aged 5-6 years before and after being given treatment to form food creation that is from 143.67 during pretest to 168.37 at posttest, resulting in an increase in scores of 24.70. Conclusions based on these data, there is a significant increase in the picky eater behavior of children aged 5-6 years at TK Negeri Pembina, Pemalang Regency after being treated with demonstration methods for forming food creations, and there are several other methods for overcoming picky eater behavior, including conversing questions and answers, storytelling, and role-playing.